Asymmetric Effect of Oil Shocks on Food Prices in Nigeria: A Non Linear Autoregressive Distributed Lags Analysis - Shehu, Abdulaziz; Abdullah, Shafii Sayuti; Yau, Nasiru Alhaji (International Journal of Energy Economics and Policy, 2019)
This paper examines the asymmetric effect of oil shocks on food prices in Nigeria, using quarterly time series data for the period of January 2010 to December, 2017. Non Linear Autoregressive distributive lag framework was used to analyse both the asymmetric short run and long run effect of oil shocks on food prices. The results indicate that positive oil price shocks have a positive and significant effect on food price while negative changes have no significant effect on food prices. Thus, the paper suggests the need for the government to strengthen its effort in the development of agricultural sector as well as diversifying its sources of income. There is also need for an institution that is mandated to save and invest the excess liquidity that arises from positive oil shocks in the development of agricultural sector and other sectors of the economy. Keywords: Asymmetric, Oil Price Shocks, Food Prices, Non Linear Auto regressive Distributive Lag, Nigeria JEL Classifications: B4, E3 DOI: https://doi.org/10.32479/ijeep.7319